High uric acid model in Caenorhabditis elegans - Zhenjing Li; Yibin Xue; Nifei Wang; Jingli Cheng; Xiaoying Dong; Qingbin Guo; Changlu Wang (Food Science and Human Wellness)
To establish experimental high uric acid model in C. elegans. Hypoxanthine, adenine, xanthine, and uric acid were used to treat C. elegans and then hyperuricemic C. elegans was evaluated by allopurinol. Hyperuricemic C. elegans were obtained after normal worms were treated by xanthine (0.25 mg/mL, 18 h). For hyperuricemic worms, there was a statistically significant increase in the uric acid level (p < 0.001) and a lower drug damage (p > 0.05). Moreover, the model was proved to keep a high uric acid level for up to 12 h. After given allopurinol (0.25 mg/mL, 12 h), the uric acid of hyperuricemic C. elegans had a significant reduction by 15%. Furthermore, xanthine oxidase activity in hyperuricemic C. elegans showed a statistically significant increase (p < 0.001), which resulted in a raised uric acid content. A high uric acid model with low drug damage and high efficiency and stability was established in C. elegans after simply xanthine treatment. Keywords: Hyperuricemia, C. elegans, Uric acid, Xanthine, Xanthine oxidase